Who will pay reparations on my soul? : essays - McCarthy, Jesse (Liveright Publishing Corporation, a division of W. W. Norton & Company, 2021)
"This is a very smart and soulful book. Jesse McCarthy is a terrific essayist." --Zadie Smith. A supremely talented young critic's essays on race and culture, from Toni Morrison to trap, herald the arrival of a major new voice in American letters.